Organic carrier and preparation method, conductive paste and preparation method, solar cell

By using a mixture of polymer toughening system and epoxy resin system as an organic carrier in HJT solar cells, the problems of unsustainability and low production efficiency caused by high-temperature curing of silver paste are solved, and the conductivity and production efficiency are achieved. promote.

CN114974653BInactive Publication Date: 2024-12-13SOLTRIUM ADVANCED MATERIALS TECH LTD SHENZHEN
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202210600151.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-05-30
Publication Date
2024-12-13
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the prior art, high-temperature curing of silver paste leads to problems of unsustainability of printing and low production efficiency, especially in the low-temperature curing of HJT solar cells, it is difficult to improve conductivity and production efficiency.

Method used

A mixture of polymer toughening system and epoxy resin system is used as an organic carrier. By adjusting its weight ratio, a three-dimensional network structure is formed to improve the stability and flexibility of the slurry, ensuring close contact between silver powder, and improving conductivity and production efficiency.

Benefits of technology

The efficient curing and electrical conductivity of conductive paste are achieved, avoiding the problems of excessive width of printing and excessive rigidity after curing, and improving the conductivity and production efficiency of HJT solar cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114974653B_ABST
    Figure CN114974653B_ABST
Patent Text Reader

Abstract

The present application belongs to the field of conductive paste technology, and in particular, relates to an organic carrier, a conductive paste, a preparation method, and a preparation method of a solar cell. In the first aspect of the present application, an organic carrier is provided, comprising a mixture of a polymer toughening system and an epoxy resin system, and the weight ratio of the active polymer toughening system to the epoxy resin system is 1:4 to 1:19; the epoxy resin system comprises a first epoxy resin and a curing agent, and the polymer toughening system comprises a prepolymer and a second epoxy resin. The organic carrier provided in the present application uses a polymer toughening system and an epoxy resin system as a mixture, and by adjusting the weight ratio of the polymer toughening system and the epoxy resin system, the conductivity and flexibility of the conductive paste are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of conductive pastes, and in particular relates to an organic carrier and a preparation method thereof, a conductive paste and a preparation method thereof, and a solar cell. Background Art

[0002] The silver paste used in traditional crystalline silicon cells is composed of silver powder, glass powder and organic carrier. After high-temperature sintering, the silver powders are in contact with each other by melting and recrystallization of the glass powder. At the same time, the glass powder melts and etches the SiNx layer to form an ohmic contact. Different from it, the low-temperature curing paste composition of HJT (crystalline silicon heterojunction solar cell) does not contain glass powder. After low-temperature heating and curing, the resin solidifies and shrinks at a certain temperature to form a conductive path.

[0003] HJT cells can achieve a photoelectric conversion efficiency of more than 4% higher than PECR cells, lower LCOE and a simpler production process from a theoretical perspective, and have achieved a conversion efficiency of more than 23% from a practical perspective. HJT low-temperature curing slurry is particularly important for the development of HJT cells.

[0004] In order to obtain better conductivity of HJT low-temperature slurry, flaky silver powder, micron silver powder or nano silver powder is usually selected for component matching, so that the combined silver powder is in closer contact during the curing process, the porosity is lower, and the conductivity is improved. For example, a conductive powder disclosed in CN108986952A uses a spherical conductive powder with a single peak particle size distribution as the raw material, grinds a part of it, mixes and disperses the two parts, performs surface treatment, and then uses the obtained single powder. The processing method of silver powder is simple, but the actual operation is relatively cumbersome and may not achieve the best conductive effect. For example, a method for improving the conductivity and adhesion of slurry disclosed in CN112837844A, nano-flaky silver powder and nano-spherical silver powder are added to the system as the third and fourth silver powder components respectively. In principle, the conductivity of the electrode after curing can be improved, but it will affect the viscosity and thixotropy of the slurry, which will cause printing discontinuity and affect production efficiency.

[0005] The conductivity of low-temperature curing silver paste (electrode) is not only closely related to silver powder, but also more closely related to the low-temperature curing carrier. In order to improve the conductivity of the cured silver paste and improve the work efficiency of the production line, the low-temperature curing carrier needs to shrink to a certain extent after curing so that the silver powder can be more closely in contact, and the curing speed is fast during the curing stage to improve the production speed of the production line. For example, CN113012844A discloses a resin system used for HJT low-temperature silver paste that can be quickly cured and sintered. It is mainly alicyclic epoxy resin with bisphenol epoxy resin, using cationic curing agent or imidazole curing agent, but it still needs to be cured at 150-180°C for 8-20 minutes. Japanese Patent Document No. 5916633 also mentions a conductive paste with a conductive film with a very low resistivity, but it needs to be heat treated at a low temperature below 200°C, and it also requires 30 minutes of curing time to achieve the best effect, and does not have the ability to cure quickly. Summary of the invention

[0006] In view of the prior art, the purpose of this application is to provide an organic carrier, a conductive paste and a preparation method, and a preparation method of a solar cell, aiming to solve the problems of high-temperature curing of the existing silver paste, unsustainable printing, and low production efficiency.

[0007] In order to achieve the above application purpose, the technical solution adopted in this application is as follows:

[0008] In a first aspect, the present application provides an organic carrier, comprising a mixture of a polymer toughening system and an epoxy resin system, wherein the weight ratio of the polymer toughening system to the epoxy resin system is 1:4 to 1:19;

[0009] The epoxy resin system comprises a first epoxy resin and a curing agent, and the polymer toughening system comprises a prepolymer and a second epoxy resin.

[0010] The organic carrier provided in the present application is a mixture of a polymer toughening system and an epoxy resin system. By adjusting the weight ratio of the polymer toughening system and the epoxy resin system, the overall performance of the organic carrier and its stability can be improved. The epoxy resin system includes a first epoxy resin and a curing agent. The polymer toughening system is obtained by pre-reacting a prepolymer and a second epoxy resin. The curing agent can ensure that the first epoxy resin and the polymer toughening system are cured under certain conditions to form a three-dimensional network structure. The active polymer toughening system can enhance the initial thixotropy and dimensional stability of the slurry. In the pre-curing stage, it can provide a certain cohesive force to avoid the slurry from collapsing due to low cohesion, causing the printing width to be too wide and affecting the final battery efficiency. After the first epoxy resin and the polymer toughening system are completely cured, they have a certain toughness in the system to avoid excessive rigidity and brittleness after curing, thereby improving the flexibility of the electrode after curing.

[0011] The second aspect of the embodiment of the present application provides a method for preparing an organic carrier, comprising the following steps:

[0012] Mixing the first epoxy resin and the curing agent to obtain an epoxy resin system;

[0013] The second epoxy resin and the prepolymer are mixed and subjected to a ring-opening polymerization reaction to obtain a polymer toughening system;

[0014] The epoxy resin system and the polymer toughening system are mixed in a weight ratio of 1:4 to 1:19 to obtain an organic carrier.

[0015] In the present application, the first epoxy resin and the curing agent are mixed, at which time, the first epoxy resin and the curing agent do not undergo a curing reaction, and the second epoxy resin and the prepolymer participate in a ring-opening polymerization reaction to generate a polymer toughening system. The epoxy resin system and the polymer toughening system are mixed to facilitate subsequent curing and coating treatments. By regulating the weight ratio of the polymer toughening system to the epoxy resin system, the overall performance of the organic carrier is improved.

[0016] The third aspect of the present application provides a conductive paste, comprising a mixture of the organic carrier of the present application, a conductive agent and a solvent.

[0017] The conductive paste is formed by compounding the organic carrier, the conductive agent and the solvent provided in the above-mentioned embodiment of the present application. The conductive agent gives the conductive paste conductive properties. The organic carrier and the conductive agent are dispersed in the solvent, which facilitates the coating treatment of the conductive paste to form a conductive layer.

[0018] A fourth aspect of the present application provides a method for preparing a conductive paste, comprising the following steps:

[0019] Mixing the organic carrier, conductive agent and solvent of the present application to obtain a first mixture;

[0020] The first mixture is filtered to obtain a conductive paste.

[0021] The present application will include the above-mentioned organic carrier, conductive agent, and solvent of the present application, and the organic carrier, conductive agent, and solvent are mixed with each other to obtain a first mixture. The first mixture is subjected to a three-roll treatment using a three-roll mill, and the first mixture can be further dispersed to obtain a second mixture. The second mixture is filtered to remove impurities, which is convenient for subsequent treatment of the conductive paste.

[0022] The fifth aspect of the present application provides a method for preparing a solar cell, comprising a substrate and an electrode bonded to the substrate, wherein the electrode is formed by curing a conductive paste prepared by the conductive paste or the conductive paste preparation method provided by the present application.

[0023] The solar cells provided in the present application include HJT solar cells. The conductive paste of the present application can form a conductive layer on a substrate through screen printing. The conductive paste is cured, and the first epoxy resin and the second epoxy resin in the organic carrier are cured to form a three-dimensional network structure in which the conductive agent is dispersed. During the curing process, the organic matter on the surface of the conductive agent will decompose to form a conductive path, thereby increasing the conductivity of the solar cell. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 A schematic structural diagram of a first conductive agent provided by an embodiment of the present invention;

[0025] Figure 2 A schematic structural diagram of a second conductive agent provided by an embodiment of the present invention;

[0026] Figure 3 A schematic structural diagram of a third conductive agent provided by an embodiment of the present invention;

[0027] Figure 4 A schematic structural diagram of a fourth conductive agent provided in an embodiment of the present invention. DETAILED DESCRIPTION

[0028] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0029] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.

[0030] In the present application, "at least one" means one or more, and "more than one" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c", can all mean: a, b, c, ab (i.e. a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.

[0031] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the implementation regulations of this application.

[0032] The terms used in the embodiments of the present application are only for the purpose of describing specific implementation rules, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the implementation rules of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0033] The weight of the relevant components mentioned in the embodiment description of the present application can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the embodiment description of the present application, it is within the scope disclosed in the embodiment description of the present application. Specifically, the mass described in the embodiment description of the present application can be a mass unit known in the chemical industry such as μg, mg, g, kg, etc.

[0034] The terms "first" and "second" are used only for descriptive purposes to distinguish objects such as substances from each other, and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. For example, without departing from the scope of the implementation regulations of this application, the first XX can also be called the second XX, and similarly, the second XX can also be called the first XX. Therefore, the features defined as "first" and "second" can explicitly or implicitly include one or more of the features.

[0035] A first aspect of an embodiment of the present application provides an organic carrier, comprising a mixture of a polymer toughening system and an epoxy resin system, and the weight ratio of the polymer toughening system to the epoxy resin system is 1:4 to 1:19; wherein the epoxy resin system comprises a first epoxy resin and a curing agent, and the polymer toughening system comprises a prepolymer and a second epoxy resin.

[0036] The organic carrier provided in the embodiment of the present application is a mixture of a polymer toughening system and an epoxy resin system. On the one hand, by adjusting the weight ratio of the polymer toughening system and the epoxy resin system, specifically, the weight ratio of the polymer toughening system and the epoxy resin system can be 1:10, the overall performance of the organic carrier can be improved and its stability can be improved. On the second hand, the epoxy resin system includes a first epoxy resin and a curing agent. The polymer toughening system is obtained by pre-reacting a prepolymer and a second epoxy resin. The curing agent can ensure that the first epoxy resin and the polymer toughening system are cured under certain conditions to form a three-dimensional network structure. The active polymer toughening system can enhance the initial thixotropy and dimensional stability of the slurry. On the third hand, the polymer toughening system can provide a certain cohesive force in the curing stage to avoid the slurry from collapsing due to low cohesion, causing the printing width to be too wide and affecting the final battery efficiency. After the first epoxy resin and the polymer toughening system are completely cured, the polymer toughening system will have a certain toughness to avoid excessive rigidity and brittleness after curing, thereby improving the flexibility of the electrode after curing.

[0037] In some embodiments, the weight ratio of the first epoxy resin, the curing agent, the prepolymer and the second epoxy resin is 100:(1-3):(0.5-3):(3-20). By adjusting the ratio of the first epoxy resin, the curing agent, the prepolymer and the second epoxy resin, the overall performance of the organic carrier can be further improved.

[0038] In some embodiments, the first epoxy resin is used as the matrix component of the organic carrier of the embodiment of the present application, so that the organic carrier can play the physical and chemical functions of the thermosetting resin, such as generating infusible and insoluble substances after curing, and having good mechanical properties. The first epoxy resin includes at least one of bisphenol A epoxy resin, bisphenol F epoxy resin, phenolic epoxy resin, o-cresol epoxy resin, and alicyclic epoxy resin. The first epoxy resin provided in the embodiment of the present application can be cured to form a three-dimensional network structure. Furthermore, the first epoxy resin includes one of phenolic epoxy resin and alicyclic epoxy resin. In the embodiment of the present application, the weight percentage of the epoxy resin system is 100%, and the mass fraction of the first epoxy resin as the matrix component of the organic carrier is 99%, but it is not limited to this.

[0039] In some embodiments, the epoxy equivalent of the first epoxy resin is 130 to 400 g / eq. Further, the epoxy equivalent of the first epoxy resin is 150 to 300 g / eq, and the curing agent is at least one of a Lewis acid complex salt or dicyandiamide. The epoxy resin system formed by the first epoxy resin and the curing agent in the embodiment of the present application has a fast curing speed, and the shrinkage effect produced during curing can promote the contact between the conductive agents, so that the conductive agents can transfer electrons more effectively, thereby improving the conductivity.

[0040] In some embodiments, the curing agent is used as a curing component of the organic carrier of the embodiment of the present application, and the curing agent includes at least one of anhydride, imidazole, Lewis acid complex salt, polyamine, tertiary amine, and dicyandiamide. Further, the curing agent includes at least one of Lewis acid complex salt or dicyandiamide. In the embodiment of the present application, the mass percentage of the curing agent is 1% based on the weight percentage of the epoxy resin system as 100%, but it is not limited thereto.

[0041] In some embodiments, the second epoxy resin curing agent is used as a toughening component of the organic vehicle of the present application embodiment, and the second epoxy resin includes a compound as shown in structure Ⅰ:

[0042]

[0043] Wherein, R1 is —(CH2) n —, n = 1 to 9, R2 is n=1 to 5. In some embodiments, the second epoxy resin includes at least one of a compound with structure Ⅱ, a compound with structure Ⅲ, and a compound with structure Ⅳ;

[0044]

[0045]

[0046] In some embodiments, at a temperature of 25°C, the viscosity of the second epoxy resin is less than 50mPa·s. The polymer toughening system formed by mixing the second epoxy resin and the prepolymer can enhance the initial thixotropy and dimensional stability of the slurry. In the precuring stage, it can provide a certain cohesion to avoid the slurry from collapsing due to low cohesion, causing the printing width to be too wide, affecting the final battery efficiency. After the organic carrier is completely cured, it has a certain toughness in the system to avoid excessive rigidity and brittleness after curing, and improve the flexibility of the electrode after curing. In the embodiment of the present application, the weight percentage of the polymer toughening system is 100%, and the mass percentage of the prepolymer is 1%. For example, the second epoxy resin is 1%, but it is not limited to this. In the embodiment of the present application, the weight percentage of the polymer toughening system is 100%, and the mass percentage of the second epoxy resin is 1%, but it is not limited to this.

[0047] In some embodiments, the prepolymer includes at least one of a polyurethane prepolymer, a phenolic resin prepolymer, and an amino prepolymer, which can further improve the toughness of the organic carrier.

[0048] The second aspect of the embodiment of the present application provides a method for preparing an organic carrier, comprising the following steps:

[0049] Step S10: mixing the first epoxy resin and the curing agent to obtain an epoxy resin system;

[0050] Step S20: mixing the second epoxy resin and the prepolymer and subjecting them to a ring-opening polymerization reaction to obtain a polymer toughening system;

[0051] Step S30: mixing the epoxy resin system and the polymer toughening system in a weight ratio of 1:4 to 1:19 to obtain an organic carrier.

[0052] In the first aspect of the embodiment of the present application, a first epoxy resin and a curing agent are mixed. At this time, the first epoxy resin and the curing agent do not undergo a curing reaction. The second epoxy resin and the prepolymer participate in a ring-opening polymerization reaction to generate a polymer toughening system. In the second aspect, the epoxy resin system and the polymer toughening system are mixed to facilitate subsequent curing and coating treatments. In the third aspect, the weight ratio of the polymer toughening system to the epoxy resin system is adjusted to improve the overall performance of the organic carrier.

[0053] In the above step S20, the mixing treatment and the ring-opening polymerization reaction specifically include the following steps:

[0054] heating the second epoxy resin to 40° C. to obtain a preheated product;

[0055] Slowly adding the prepolymer to the preheated material and mixing the prepolymer to obtain a mixture;

[0056] The mixture is heated to 75-85°C at a heating rate of 5°C / h and then kept warm for 1-3 hours to obtain a polymer toughening system. The embodiment of the present application can further control the reaction rate of the ring-opening polymerization reaction and control the polymerization degree of the reaction.

[0057] In some embodiments, the second epoxy resin is heated to 40°C, and then the high molecular polymer is slowly added, stirred until homogeneous, and then heated to 80°C at a heating rate of 5°C / h and kept warm for 2h to prepare a polymer toughening system. Slowly adding the high molecular polymer can make the low viscosity epoxy resin and the high molecular polymer disperse more evenly, reduce the initial reaction, and react more smoothly when reaching 80°C, so that the prepared polymer toughening system has a narrow molecular weight distribution and is easier to mix with the subsequent epoxy system.

[0058] A third aspect of the embodiments of the present application provides a conductive paste, comprising a mixture of the organic carrier, the conductive agent and the solvent of the embodiments of the present application.

[0059] The conductive paste is formed by compounding the organic carrier provided in the above-mentioned embodiment of the present application with a conductive agent and a solvent. The conductive agent gives the conductive paste conductive properties. The organic carrier and the conductive agent are dispersed in the solvent to facilitate coating of the conductive paste to form a conductive layer.

[0060] In some embodiments, the weight ratio of the conductive agent, the organic carrier and the solvent is (90-95):(4-7):(1-3). In the entire conductive paste component, by adjusting the proportion of the solvent, the system viscosity can be adjusted so that the conductive paste is not too thin or too thick, thereby improving the feasibility of paste printing.

[0061] In some embodiments, the solvent can effectively disperse the conductive agent and the organic carrier. The solvent provided in the embodiments of the present application includes at least one of ethyl cellosolve, butyl cellosolve, butyl cellosolve acetate, diethylene glycol diethyl ether, butyl carbitol, diethylene glycol butyl ether acetate, carbitol butyl ether acetate, glycol ether acetate, diacetone alcohol, pinene alcohol, benzyl alcohol, cyclohexanone, methyl ethyl ketone, DBE, 2,2,4-trimethyl-1,3-pentanediol monoisobutyl ester, and 2,2,4-trimethyl-1,3-pentanediol diisobutyl ester.

[0062] In some embodiments, the conductive agent includes at least one of the following first conductive agent, second conductive agent, third conductive agent, fourth conductive agent and fifth conductive agent, such as Figure 1 As shown, the first conductive agent includes silver particles and organic matter coated on the surface of the silver particles, such as Figure 2 As shown, the second conductive agent includes copper particles, a silver layer coated on the surface of the copper particles, and an organic substance coated on the surface of the silver layer, such as Figure 3 As shown, the third conductive agent includes copper particles, a nickel layer coated on the surface of the copper particles, and a first metal layer coated on the surface of the nickel layer, such as Figure 4 As shown, the fourth conductive agent includes copper particles, a second metal layer coated on the surface of the copper particles, and an organic substance coated on the surface of the second metal layer, and the fifth conductive agent includes an alloy formed by at least two of tin, silver and indium. On the one hand, the organic substance on the surface of the conductive agent improves the dispersibility of the conductive agent in the organic carrier and prevents the conductive agent from agglomerating. On the other hand, the outermost layers of the first, second and fourth conductive agents are all low-temperature dissociable organic substances, which can be dissociated within the curing temperature (180-220°C) required by the low-temperature silver paste so that the conductive metal can be in better close contact and the conductivity can be improved, or they can be removed by the flux in the subsequent welding process to facilitate better combination with the solder to form a solid solder joint.

[0063] Specifically, the mass ratio of the fifth conductive agent in all conductive agents is 0.1-2wt%, and the fifth conductive agent includes at least one of the following components (A), (B), (C), (D), (E), and (F).

[0064] (A) When the mass of the fifth conductive agent is 100, the mass proportion of In is 97% and the mass proportion of Ag is 3%.

[0065] (B) When the mass of the fifth conductive agent is 100%, the mass proportion of In is 52%, and the mass proportion of Sn is 48%.

[0066] (C) When the mass of the fifth conductive agent is 100%, the mass proportion of Ag is 10%, and the mass proportion of In is 90%.

[0067] (D) When the mass of the fifth conductive agent is 100%, the mass proportion of Sn is 99.3%, and the mass proportion of Cu is 0.7%.

[0068] (E) When the mass of the fifth conductive agent is taken as 100, the mass proportion of Sn is 96.5%, the mass proportion of Ag is 3.0%, and the mass proportion of Cu is 0.5%.

[0069] (F) Taking the mass of the fifth conductive agent as 100%, the mass of Sn accounts for 99%, the mass of Ag accounts for 0.3%, and the mass of Cu accounts for 0.7%. The melting point of the fifth conductive agent in the embodiment of the present application is below 230°C. During the low-temperature drying stage in the electrode manufacturing process, it can diffuse and fuse with silver particles or silver-coated copper particles to increase the bonding between silver particles or silver-coated copper particles and thus improve their electrical conductivity. In the subsequent high-temperature welding process, the fifth conductive agent can further promote the bonding and electrical conductivity between silver particles or silver-coated copper particles through its diffusion, and form a good metallurgical bond with the solder material, thereby improving the bonding force between the solder material and the electrode.

[0070] In some embodiments, the organic matter includes at least one of benzotriazole, copper benzotriazole, imidazole, copper imidazole, benzimidazole, and copper benzimidazole. The organic matter provided in the embodiments of the present application can make the conductive agent evenly dispersed in the organic carrier, and under certain curing conditions, it can decompose to promote the contact between the conductive agents and increase the conductivity of the conductive paste.

[0071] In some embodiments, the first metal layer and the second metal layer are each independently selected from one of silver, tin and solder, which can further improve the conductivity of the conductive paste.

[0072] In some embodiments, the conductive agent has a shape including at least one of spherical, quasi-spherical, flake, quasi-flake, and dendritic. Figures 1 to 4 A spherical shape is shown, but is not limited to such.

[0073] A fourth aspect of the present application provides a method for preparing a conductive paste, comprising the following steps:

[0074] Step S40: mixing the organic carrier, the conductive agent, and the solvent according to the embodiment of the present application to obtain a first mixture;

[0075] Step S50: filtering the first mixture to obtain a conductive paste.

[0076] The embodiment of the present application will include the above-mentioned embodiment of the present application, the organic carrier, the conductive agent, and the solvent are mixed together to obtain a first mixture, and the first mixture is subjected to a three-roll process using a three-roll mill to further disperse the first mixture to obtain a second mixture, and the second mixture is filtered to remove impurities, thereby facilitating subsequent processing of the conductive paste.

[0077] The above step S40 also includes the step of preparing a conductive agent. Low-temperature dissociable organic coating process: weigh 10 g of the low-temperature dissociable organic coating and add it to 100 g of a 3% acetic acid ethanol solution for standby use, then add silver, silver-coated copper or copper coated with two layers of metal into the low-temperature dissociable organic coating solution and soak for 1 min, filter and wash, and use as the first, second or fourth conductive agent.

[0078] In some embodiments, the metal particles of the second conductive agent are copper particles coated with silver. The specific method is: the copper powder is ultrasonically washed with dilute acid and then prepared into a copper powder suspension. The reducing agent sodium hypophosphite is added to the copper powder suspension, and the pH is adjusted to 10-11 with sodium hydroxide, and then the silver ammonia solution is slowly added, and filtered and washed after ultrasonic stirring. The washed powder is placed in an electric blast drying oven and dried at 80°C for 2 hours to obtain the metal particles of the second conductive agent, and then a low-temperature dissociable organic coating process is performed to prepare the second conductive agent.

[0079] In some embodiments, the third conductive agent is a two-layer metal layer coated on the surface of copper particles. After the copper powder is ultrasonically washed with dilute acid, a nickel sulfate solution is added, and the pH is adjusted to 4-5 with acetic acid, and then a sodium hypophosphite solution is added dropwise, and filtered and washed after ultrasonic stirring. The washed powder is formulated into a suspension, and the reducing agent glucose is added after ultrasonication at 60°C for 30 minutes, and the pH is adjusted to 10-11 with sodium hydroxide, and then a silver ammonia solution is slowly added, and the ultrasonic reaction is continued for 30 minutes before filtering and washing. The washed powder is placed in an electric hot air drying oven and dried at 80°C for 2 hours to obtain the third conductive agent.

[0080] A fifth aspect of an embodiment of the present application provides a solar cell, comprising a substrate and an electrode coupled to the substrate, wherein the electrode is formed by curing a conductive paste prepared by the conductive paste or preparation method provided by the above-mentioned embodiment of the present application.

[0081] The solar cell provided in the embodiment of the present application includes an HJT solar cell. The conductive paste of the above-mentioned embodiment of the present application can form a conductive layer on a substrate through screen printing. After the conductive paste is cured, the first epoxy resin and the second epoxy resin in the organic carrier will be cured to form a three-dimensional network structure, in which the conductive agent is dispersed. During the curing process, the organic matter on the surface of the conductive agent will decompose to form a conductive path, thereby increasing the conductivity of the solar cell.

[0082] In some embodiments, the opening width of the screen printing process is ≤24 μm. In some embodiments, the curing temperature is 160-180° C. and the curing time is 3-10 min. The conductive paste provided in the embodiment of the present application has a low curing temperature and a short curing time, which can improve production efficiency.

[0083] In order to enable the above-mentioned implementation details and operations of the present application to be clearly understood by those skilled in the art, as well as to demonstrate the significant improvement in the performance of the organic carrier and preparation method, the conductive paste and preparation method, and the solar cell in the embodiments of the present application, the above-mentioned technical scheme is illustrated by means of multiple embodiments below.

[0084] Example 1

[0085] In a first aspect, the present embodiment provides an organic carrier, comprising a mixture of a polymer toughening system and an epoxy resin system, wherein the weight ratio of the active polymer toughening system to the epoxy resin system is 1:10;

[0086] The epoxy resin system includes phenolic epoxy resin and Lewis acid complex salt, and the polymer toughening system includes polyurethane prepolymer and a compound with a structure as shown in Ⅱ.

[0087] A second aspect of the present embodiment provides a conductive paste, comprising an organic carrier, a first conductive agent, a fifth conductive agent and terpineol in a mass ratio of 5:92.5:0.5:2.

[0088] A third aspect of the present embodiment provides a method for preparing a conductive paste, comprising the following steps:

[0089] S111: Based on the mass percentage of the epoxy resin system being 100%, 99% of a novolac epoxy resin having an epoxy equivalent of 170 g / eq and 1% of a Lewis acid complex salt are mixed until a homogeneous phase is obtained, which is recorded as E-1.

[0090] S112: Based on 100 parts by mass of the polymer toughening system, 90 parts by mass of a low-viscosity epoxy resin such as the compound shown in structure Ⅱ is heated to 40°C, and then 10 parts by mass of a polyurethane prepolymer is slowly added, stirred until homogeneous, and then heated to 80°C at a heating rate of 5°C / h and kept warm for 2h to obtain a polymer toughening system, which is recorded as S-1.

[0091]

[0092] S120: Weigh 10g of benzotriazole and add it to 100g of 3% acetic acid ethanol solution for later use, then add silver powder to the benzotriazole acetic acid ethanol mixed solution, soak for 1min, filter, wash, and finally dry at 80℃ for 1h to obtain the first conductive agent, which is recorded as A-1.

[0093] S130: E-1 and S-1 were mixed at a mass ratio of 1:10 until they were homogeneous, and recorded as B-1.

[0094] S20: A-1, B-1, the fifth conductive agent and the solvent are prepared in a mass ratio of 92.5:5:0.5:2, pine alcohol is selected as the solvent, and 97In3Ag is selected as the fifth conductive agent. A-1, 97In3Ag and pine alcohol are first mixed, and then B-1 is added, and three-roll milling is used for dispersion treatment to prepare a conductive paste sample.

[0095] S30: The conductive slurry sample is filtered to obtain a conductive slurry.

[0096] A fourth aspect of the present embodiment provides a method for preparing a solar cell, comprising the following steps:

[0097] S40: The conductive paste is printed, pre-cured at 160° C. for 3 minutes, and cured at 190° C. for 5 minutes before performing relevant performance tests.

[0098] Example 2

[0099] In a first aspect, the present embodiment provides an organic carrier, comprising a mixture of a polymer toughening system and an epoxy resin system, wherein the weight ratio of the polymer toughening system to the epoxy resin system is 1:10;

[0100] The epoxy resin system includes phenolic epoxy resin and Lewis acid complex salt, and the polymer toughening system includes polyurethane prepolymer and a compound with a structure as shown in Ⅱ.

[0101] A second aspect of the present embodiment provides a conductive paste, comprising an organic vehicle, a fourth conductive agent, a fifth conductive agent, and diethylene glycol butyl ether acetate in a mass ratio of 4:92.7:0.3:3.

[0102] A third aspect of the present embodiment provides a method for preparing a conductive paste, comprising the following steps:

[0103] S111: Based on the mass percentage of the epoxy resin system being 100%, 99% of a novolac epoxy resin having an epoxy equivalent of 180 g / eq and 1% of a Lewis acid complex salt are mixed until a homogeneous phase is obtained, which is recorded as E-1.

[0104] S112: Based on the mass parts of the polymer toughening system as 100, 90 mass parts of low-viscosity epoxy resin of the compound shown in structure III are heated to 40°C, and then 10 mass parts of phenolic resin prepolymer are slowly added, stirred until homogeneous, and then heated to 80°C at a heating rate of 5°C / h and kept warm for 2h to obtain an active polymer toughening system, which is recorded as S-1.

[0105]

[0106] S121: copper powder is added to dilute acid, washed with ultrasound, and then nickel sulfate solution is added, and the pH is adjusted to 4-5 with acetic acid, and then sodium hypophosphite solution is added dropwise, and filtered and washed after ultrasonic stirring to obtain a first washed powder.

[0107] S122: The first washed powder is prepared into a suspension, and after ultrasonication for 30 minutes at 60°C, glucose as a reducing agent is added, and the pH is adjusted to 10-11 with sodium hydroxide, and finally, silver ammonia solution is slowly added, ultrasonication and reaction are carried out for 30 minutes, and then filtering and washing are performed to obtain the second washed powder.

[0108] S123: Put the second washed powder into an electric heated blast drying oven at 80° C. and dry it for 2 hours to obtain a third conductive agent.

[0109] S124: The third conductive agent is added to the mixed solution of benzimidazole and acetic acid and ethanol, and after soaking for 1 minute, the mixture is filtered and washed, and finally dried at 80° C. for 1 hour to obtain the fourth conductive agent, which is recorded as A-1.

[0110] S130: E-1 and S-1 were mixed at a mass ratio of 1:10 until they were homogeneous, and recorded as B-1.

[0111] S20: Prepare materials according to the mass ratio of A-1, B-1, the fifth conductive agent and the solvent of 92.7:4:0.3:3, the solvent is diethylene glycol butyl ether acetate, and the fifth conductive agent is 52In48Sn. First, A-1, 52In48Sn and pinene alcohol are mixed, and then B-1 is added, and three-roll milling is used for dispersion treatment to prepare a conductive paste sample.

[0112] S30: The conductive slurry sample is filtered to obtain a conductive slurry.

[0113] A fourth aspect of the present embodiment provides a method for preparing a solar cell, comprising the following steps:

[0114] S40: After the conductive paste is printed, it is pre-cured at 160°C for 3 minutes and cured at 190°C for 5 minutes before performing relevant performance tests.

[0115] Example 3

[0116] In a first aspect, the present embodiment provides an organic carrier, comprising a mixture of a polymer toughening system and an epoxy resin system, wherein the weight ratio of the polymer toughening system to the epoxy resin system is 1:10;

[0117] The epoxy resin system includes phenolic epoxy resin and Lewis acid complex salt, and the polymer toughening system includes polyurethane prepolymer and a compound with a structure as shown in Ⅱ.

[0118] A second aspect of the present embodiment provides a conductive paste, including an organic vehicle, the sum of the masses of a first conductive agent and a fourth conductive agent, and a fifth conductive agent and DBE in a mass ratio of 4:92.5:0.5:3.

[0119] A third aspect of the present embodiment provides a method for preparing a conductive paste, comprising the following steps:

[0120] S111: Based on the mass percentage of the epoxy resin system being 100%, 99% of a phenolic epoxy resin having an epoxy equivalent of 190 g / eq and 1% of a Lewis acid complex salt are mixed until a homogeneous phase is obtained, which is recorded as E-1.

[0121] S112: Based on 100 parts by mass of the polymer toughening system, 90 parts by mass of the epoxy resin of the compound shown in structure IV are heated to 40°C, and then 10 parts by mass of phenolic resin prepolymer are slowly added, stirred until homogeneous, and then heated to 80°C at a heating rate of 5°C / h and kept warm for 2h to obtain an active polymer toughening system, recorded as S-1.

[0122]

[0123] S121: copper powder is added to dilute acid, washed with ultrasound, and then nickel sulfate solution is added, and the pH is adjusted to 4-5 with acetic acid, and then sodium hypophosphite solution is added dropwise, and filtered and washed after ultrasonic stirring to obtain a first washed powder.

[0124] S122: The first washed powder is prepared into a suspension, and after ultrasonication for 30 minutes at 60°C, glucose as a reducing agent is added, and the pH is adjusted to 10-11 with sodium hydroxide, and finally, silver ammonia solution is slowly added, ultrasonication and reaction are carried out for 30 minutes, and then filtering and washing are performed to obtain the second washed powder.

[0125] S123: Put the second washed powder into an electric heated blast drying oven at 80° C. and dry it for 2 hours to obtain a third conductive agent.

[0126] S124: Add the third conductive agent and silver powder in a mass ratio of 1:1 to a mixed solution of benzimidazole and acetic acid ethanol, soak for 1 minute, filter, wash, and finally dry at 80° C. for 1 hour to obtain a mixture of the first and fourth conductive agents, which is recorded as A-1.

[0127] S130: E-1 and S-1 are mixed at a mass ratio of 1:15 until they become homogeneous, and the mixture is recorded as B-1.

[0128] S20: Prepare materials according to the mass ratio of A-1, B-1, the fifth conductive agent, and the solvent of 92.5:4:0.5:3, select DBE as the solvent, and select 97In3Ag as the fifth conductive agent. First, mix A-1, 97In3Ag, and pineneol, then add B-1, disperse, and grind with three rollers to prepare a conductive paste sample.

[0129] S30: The conductive slurry sample is filtered to obtain a conductive slurry.

[0130] A fourth aspect of the present embodiment provides a method for preparing a solar cell, comprising the following steps:

[0131] S40: After the conductive paste is printed, it is pre-cured at 160°C for 3 minutes and cured at 190°C for 5 minutes before performing relevant performance tests.

[0132] Comparative Example 1

[0133] This comparative example provides a conductive paste, including an organic carrier, a first conductive agent, a fifth conductive agent and pineol in a mass ratio of 5:92.5:0.5:2, and based on the mass percentage of the organic carrier being 100%, the organic carrier includes 99% phenolic epoxy resin and 1% Lewis acid composite salt.

[0134] Comparative Example 2

[0135] This ratio provides a conductive paste, including an organic carrier, a first conductive agent and pine alcohol in a mass ratio of 5:93:0.5:2, and based on the mass percentage of the organic carrier being 100%, the organic carrier includes 99% phenolic epoxy resin and 1% Lewis acid composite salt.

[0136] Comparative Example 3

[0137] This comparative example provides a conductive paste, including an organic carrier, commercially available silver powder Metalor P900, a fifth conductive agent and pineol in a mass ratio of 4:92.5:0.5:3, and based on the mass percentage of the organic carrier being 100%, the organic carrier includes 99% phenolic epoxy resin and 1% Lewis acid complex salt.

[0138] Performance Testing

[0139] The conductive pastes in Examples 1 to 3 and Comparative Examples 1 to 3 were subjected to performance tests.

[0140] Table 1 Performance test results

[0141]

[0142]

[0143] The difference between Examples 1 to 3 and Comparative Example 1 is that Comparative Example 1 does not introduce an active polymer toughening system. Specifically, as shown in Table 1, the introduction of the active polymer toughening system in Examples 1 to 3 can greatly reduce the resistance of the conductive paste, improve the adhesion level, and greatly improve the welding tensile force. Therefore, the conductive pastes in Examples 1 to 3 are suitable for HJT solar cells.

[0144] The difference between Examples 1 to 3 and Comparative Example 2 is that Comparative Example 2 does not add the fifth conductive agent (conductive alloy). Specifically, please refer to Table 1. The introduction of the fifth conductive agent (conductive alloy) in Examples 1 to 3 will slightly reduce the resistance of the conductive paste and significantly increase the welding tension.

[0145] The difference between Examples 1 to 3 and Comparative Example 3 is that the conductive agent in Comparative Example 3 is commercially available silver powder Metalor P900. Specifically, please refer to Table 1. By selecting a low-temperature dissociable organic substance to coat the conductive agent, the resistance of the conductive paste is greatly reduced and the welding tension is increased to a certain extent.

[0146] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.

Claims

1. An organic carrier, characterized in that It comprises a mixture of a polymer toughening system and an epoxy resin system, wherein the weight ratio of the polymer toughening system to the epoxy resin system is 1:4 to 1:19; The epoxy resin system includes a first epoxy resin and a curing agent, and the polymer toughening system includes a prepolymer and a second epoxy resin; The weight ratio of the first epoxy resin, the curing agent, the prepolymer and the second epoxy resin is 100:(1-3):(0.5-3):(3-20); The first epoxy resin comprises at least one of bisphenol A epoxy resin, bisphenol F epoxy resin, novolac epoxy resin, o-cresol epoxy resin, and alicyclic epoxy resin; The epoxy equivalent of the first epoxy resin is 130 to 400 g / eq; The prepolymer includes at least one of a polyurethane prepolymer, a phenolic resin prepolymer, and an amino prepolymer; At a temperature of 25° C., the viscosity of the second epoxy resin is less than 50 mPa·s; The second epoxy resin comprises at least one of a compound with a structure as shown in Formula I and a compound with a structure as shown in Formula III: Wherein, R1 is —(CH2) n —, n = 1 to 9, R2 is n = 1 to 5; 2. The organic carrier according to claim 1, characterized in that: The second epoxy resin includes at least one of a compound with structure shown in II and a compound with structure shown in IV; 3. The organic carrier according to any one of claims 1 to 2, characterized in that: The curing agent includes at least one of anhydride, imidazole, Lewis acid complex salt, polyamine, tertiary amine and dicyandiamide.

4. A method for preparing an organic carrier, characterized in that: The steps include: Mixing the first epoxy resin and the curing agent to obtain an epoxy resin system; The second epoxy resin and the prepolymer are mixed and subjected to a ring-opening polymerization reaction to obtain a polymer toughening system; The epoxy resin system and the polymer toughening system are mixed in a weight ratio of 1:4 to 1:19 to obtain an organic carrier; The weight ratio of the first epoxy resin, the curing agent, the prepolymer and the second epoxy resin is 100:(1-3):(0.5-3):(3-20); The first epoxy resin comprises at least one of bisphenol A epoxy resin, bisphenol F epoxy resin, novolac epoxy resin, o-cresol epoxy resin, and alicyclic epoxy resin; The epoxy equivalent of the first epoxy resin is 130 to 400 g / eq; The prepolymer includes at least one of a polyurethane prepolymer, a phenolic resin prepolymer, and an amino prepolymer; At a temperature of 25° C., the viscosity of the second epoxy resin is less than 50 mPa·s; The second epoxy resin comprises at least one of a compound with a structure as shown in Formula I and a compound with a structure as shown in Formula III: Wherein, R1 is —(CH2) n —, n = 1 to 9, R2 is n = 1 to 5; 5. The method for preparing an organic carrier according to claim 4, characterized in that: The mixing treatment and ring-opening polymerization reaction specifically include the following steps: heating the second epoxy resin to 40° C. to obtain a preheated product; Slowly adding the prepolymer to the preheated material and mixing the prepolymer to obtain a mixture; The mixture is heated to 75-85° C. at a heating rate of 5° C. / h and then kept warm for 1-3 hours to obtain the polymer toughening system.

6. A conductive paste, characterized in that: A mixture comprising the organic carrier according to any one of claims 1 to 3, a conductive agent and a solvent.

7. The conductive paste according to claim 6, characterized in that: The weight ratio of the conductive agent, the organic carrier and the solvent is (90-95):(4-7):(1-3); Or / and, the solvent includes at least one of ethyl cellosolve, butyl cellosolve, butyl cellosolve acetate, diethylene glycol diethyl ether, butyl carbitol, diethylene glycol butyl ether acetate, carbitol butyl ether acetate, glycol ether acetate, diacetone alcohol, terpineol, benzyl alcohol, cyclohexanone, methyl ethyl ketone, DBE, 2,2,4-trimethyl-1,3-pentanediol monoisobutyl ester, and 2,2,4-trimethyl-1,3-pentanediol diisobutyl ester.

8. The conductive paste according to claim 7, characterized in that: The conductive agent has a shape of at least one of sphere, spherical-like, flake, flake-like, fiber and dendrite; Or / and, the particle size or length of the conductive agent is 0.1 to 50 μm.

9. A method for preparing a conductive paste, characterized in that: The steps include: Mixing the organic carrier according to any one of claims 1 to 3, a conductive agent, and a solvent to obtain a first mixture; The first mixture is filtered to obtain the conductive paste.

10. The method for preparing the conductive paste according to claim 9, characterized in that: The mixing process specifically comprises the following steps: The organic carrier, the conductive agent and the solvent are subjected to a three-roll process using a three-roll mill to obtain a first mixture.

11. A solar cell, characterized in that: It comprises a substrate and an electrode bonded to the substrate, wherein the electrode is formed by curing a conductive paste prepared by the preparation method of the conductive paste according to any one of claims 6 to 8 or the conductive paste according to claim 9 or 10.

12. The solar cell according to claim 11, characterized in that: The curing temperature is 160-180° C., and the curing time is 3-10 minutes.

Citation Information

Patent Citations

  • Heat-curable conductive paste, use thereof and solar cell

    CN108986952A

  • HJT low-temperature curing silver paste with dual curing performance and preparation method of HJT low-temperature curing silver paste

    CN112837844A

  • HJT low-temperature silver paste capable of being rapidly cured and sintered and preparation method of HJT low-temperature silver paste

    CN113012844A

  • Manufacture of spinneret

    JP1984016633A

  • Preparing technology of polyurethane modified ethoxyline resin adapted for composite wear-resistant coating material

    CN101445583A